The preliminary study for determination of gut bacteria and fungi microbiota among breast cancer patients in pahang, malaysia - Darren, Dean Tay (2024)
Over the years, the number of breast cancer incidents have been steadily increasing, signaling a growing need for more relevant screening and treatment measures against it. Surprisingly, genetic predispositions account for only 10% of breast cancer cases, while half of most cases are associated with dietary intake and lifestyle. Thus, gut bacteria and fungi, commonly known as the gut microbiome may play somewhat of an active role in breast cancer formation. Many studies have associated the gut microbiome to breast cancer development, however given the unique demographics surrounding different locations and backgrounds, Asian representation can be found quite lacking especially for countries like Malaysia. As such, this study aims to compare the gut microbiomes found in breast cancer patients against those who are cancer free and relate that info to cancer formation within the context of Pahang, Malaysia. In short, both gut bacteria and fungi were analysed accordingly and correlated with each other to better understand their role towards cancer formation. This was conducted using collected stool samples from 32 breast cancer patients and 32 individuals who were cancer-free from the IIUM Medical Centre, Pahang, Malaysia. These samples were subjected to both amplicon and long reads sequencing of the 16S rRNA gene and ITS1 using a NovaSEQ6000. QIIME2 was utilized to analyse and process the obtained sequenced data to be uploaded to the MicrobiomeAnalyst webservers for further statistical analysis. The study found there were significant results upon analyzing the cohort based on direct comparison of health status, menopausal states, and BMI for both bacteria and fungi. Bacterial datasets showed no differences in species diversity across samples but observed unique bacterial compositions between groups. Fungal datasets however showed statistical significance for both alpha- and beta-diversities. Breast cancer patients were shown to be positively correlated with the genera Holdemanella, Akkermansia, Candida and unclassified Aureobasidiaceae while the control group were more associated with Anaerobutyricum, Choanephora, Trichosporon, and Aspergillus. Potential biomarkers were also able to be identified for breast cancer detection which were the bacterial genus Holdemanella and fungal genera of Aspergillus, unclassified Aureobasidiaceae, Cystobasidium, and Rhizopus. Correlation analysis depicted positive correlation and associations between the fungal genus Rhodotorula, and bacterial genera Enterococcus_B, as well as unclassified Enterococcaceae towards breast cancer patients. Other associations included unclassified Enterococcaceae, Clostridium_P, Enterococcus_B and Collinsella. Overall, the findings of this study concluded that gut microbes have a strong association and possible role within the context of breast cancer formation, though its immediate usefulness for clinical use is not yet known. More studies would be required in the future to further build upon these findings to a point where it would be relevant for clinical use.